Dynamic triggering of high‐frequency bursts by strong motions during the 2004 Parkfield earthquake sequence - Adam D. Fischer; Zhigang Peng; Charles G. Sammis (Geophysical Research Letters)
High‐pass filtering (>20 Hz) of acceleration records from the USGS Parkfield Dense Seismograph Array (UPSAR) reveals a series of bursts that occur only during strong shaking from the 2004 Mw6 Parkfield, California, earthquake and its immediate aftershocks. Because there is no correlation between these high frequency bursts observed at closely spaced stations, we hypothesize that they are associated with dynamically triggered events occurring within 20 meters of the stations in the highly fractured shallow crust. The triggering threshold was found to be ∼0.02 MPa, consistent with a previous estimate based on a similar analysis of high‐frequency bursts observed in strong motion data from the 1999 Chi‐Chi earthquake in Taiwan (Fischer et al., 2008). The consistent observation of high‐frequency bursts at both Parkfield and Taiwan suggest that they may be a common phenomenon associated with strong motion in the very shallow crust.